Experimental study on the mechanical properties of freeze-thaw cycled sandstone under dynamic loading - Xu, Hanhua; Sui, Sugang; Zou, Junpeng; Bao, Xun; Tian, Weijie; He, Shijing; Zhang, Quan (Frontiers in Earth Science, 2025)
China’s western alpine regions are rich in mineral resources. However, factors such as freeze-thaw erosion, earthquakes, rainfall, and mining disturbances have weakened the strength of rock masses in alpine mine slopes, leading to structural weathering. These issues severely compromise the safety and stability of rock slopes and hinder the safe, efficient production of mineral resources. Both impact loads (such as blasting) and seismic loads can induce instantaneous deformation in structures and their components, sharing similar mechanisms of action. Therefore, this study conducts dynamic impact tests on sandstone based on the research context of impact loads including seismic events and excavation blasting. This study focuses on the Lanping Lead-Zinc Mine. First, through freeze-thaw cycle tests, SHPB (Split Hopkinson Pressure Bar) impact tests, and DIC (Digital Image Correlation) technology, the impact mechanical responses and failure characteristics of sandstone specimens under different freeze-thaw cycles were investigated. The dynamic mechanical properties and crack propagation patterns of sandstone under impact loading at various freeze-thaw cycles were revealed. The findings indicate that the strain rate ε´-t curve of sandstone specimens under dynamic impact is characterized by “increasing-stabilizing-accelerating decrease”. The strain (ε-t) curve initially increases before stabilizing, and the peak strain rises with the number of freeze-thaw cycles. The stress-strain response of sandstone under impact loading can generally be divided into three stages: linear elastic, nonlinear hardening, and strain softening. The slope of the stress-strain curve in the elastic stage decreases as the number of freeze-thaw cycles increases. The dynamic peak stress and dynamic elastic modulus of sandstone gradually decrease with increasing freeze-thaw cycles. Analysis of the dynamic evolution of Y-directional strain in sandstone specimens under impact loading using DIC technology reveals that crack propagation is closely linked to strain concentration zones on the specimen surface. The distribution of axial strain concentration zones determines the initiation and expansion of primary and secondary cracks during specimen failure. The conclusions of this study provide theoretical insights for disaster prevention and control (e.g., frost heave and dynamic loading) in rock slope engineering in alpine mining regions.